Effects of different moisture and temperature levels on Salmonella survival in poultry fat. Issue 4 (19th June 2019) - Trinetta, Valentina; McDaniel, Austin; Magossi, Gabriela; Yucel, Umut; Jones, Cassandra
Abstract: Fat products have been historically thought to have too low water activity to harbor pathogens. However, it has been recently reported that high moisture levels in fats may lead to Salmonella presence and growth. Limited research on strategies to eliminate pathogens in these environments is available, and the mechanisms contributing to microbial presence and growth are not yet well understood. The purpose of this research was to evaluate the effects of moisture levels and storage temperatures on the growth and survival of Salmonella in poultry fat. Samples were stored for 7 d at 48°C or 76°C and remaining Salmonella was evaluated. When poultry fat was challenged with a wet high inoculum, more than a 4 log CFU/mL difference in Salmonella population was observed with 1% and 3% moisture levels at 48°C after 5 d ( P < 0.05). No differences between moisture levels ( P > 0.05) were observed when samples were tested with a wet low inoculum. Counts below detectable limits were observed after 24 h in samples challenged at 76°C, regardless of inoculum level. When poultry fat was stored at 48°C and inoculated with low levels of Salmonella spp., bacterial growth was influenced only by time ( P < 0.05) and not affected ( P > 0.05) by moisture level. However, when poultry fat was stored at 48°C and inoculated with high levels of Salmonella spp., bacterial decrease was easier ( P < 0.05) in samples containing greater moisture. This research suggests that residual moisture in containers during transportation of poultry fat largely does not affect Salmonella spp. growth.